The study of surface wetting, nanobubbles and boundary slip with an applied voltage: A review - Pan, Yunlu; Bhushan, Bharat; Zhao, Xuezeng (Beilstein Journal of Nanotechnology, 2014)
The drag of fluid flow at the solid–liquid interface in the micro/nanoscale is an important issue in micro/nanofluidic systems. Drag depends on the surface wetting, nanobubbles, surface charge and boundary slip. Some researchers have focused on the relationship between these interface properties. In this review, the influence of an applied voltage on the surface wettability, nanobubbles, surface charge density and slip length are discussed. The contact angle (CA) and contact angle hysteresis (CAH) of a droplet of deionized (DI) water on a hydrophobic polystyrene (PS) surface were measured with applied direct current (DC) and alternating current (AC) voltages. The nanobubbles in DI water and three kinds of saline solution on a PS surface were imaged when a voltage was applied. The influence of the surface charge density on the nanobubbles was analyzed. Then the slip length and the electrostatic force on the probe were measured on an octadecyltrichlorosilane (OTS) surface with applied voltage. The influence of the surface charge on the boundary slip and drag of fluid flow has been discussed. Finally, the influence of the applied voltage on the surface wetting, nanobubbles, surface charge, boundary slip and the drag of liquid flow are summarized. With a smaller surface charge density which could be achieved by applying a voltage on the surface, larger and fewer nanobubbles, a larger slip length and a smaller drag of liquid flow could be found.
Keywords: atomic force microscopy; boundary slip; electrowetting; nanobubbles; surface charge